2018
DOI: 10.1007/s00421-018-3837-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aerobic walking and lower body resistance exercise on serum COMP and hyaluronan, in both males and females

Abstract: The effect of a single bout of lower body exercise on serum COMP and HA is independent of exercise modality in healthy men and women. Furthermore, having thicker femoral cartilage and higher baseline COMP in males does not appear to influence how the cartilage responds to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
(64 reference statements)
1
16
2
Order By: Relevance
“…The substantial variability in the response to drop jumps is likely to be related to protocol differences as well as the participants studied, i.e., the greatest increase (+30.9%) was found in sedentary individuals. Following a typical lower body resistance exercise bout in healthy individuals, COMP responded in a similar manner to walking exercise of the same duration (Roberts et al 2018). Overall, the response of COMP across exercise modalities is generally similar, especially when assessing the response following walking, resistance training, and drop jumps (Fig.…”
Section: Acute Serum Biomarker Response To Joint Loadingmentioning
confidence: 94%
See 2 more Smart Citations
“…The substantial variability in the response to drop jumps is likely to be related to protocol differences as well as the participants studied, i.e., the greatest increase (+30.9%) was found in sedentary individuals. Following a typical lower body resistance exercise bout in healthy individuals, COMP responded in a similar manner to walking exercise of the same duration (Roberts et al 2018). Overall, the response of COMP across exercise modalities is generally similar, especially when assessing the response following walking, resistance training, and drop jumps (Fig.…”
Section: Acute Serum Biomarker Response To Joint Loadingmentioning
confidence: 94%
“…Of the aforementioned biomarkers, the acute response of serum hyaluronan has received the most attention, perhaps a result of its promise as a biomarker of osteoarthritis. In healthy individuals, neither an acute bout of walking or resistance training increased concentration of hyaluronan (Roberts et al 2018). This supports an early study by Engström-Laurent et al (1987) who also found no evidence of a change in hyaluronan following moderate-intensity cycling, although a bout of heavy cycling exercise resulted in a significant increase in hyaluronan.…”
Section: Acute Serum Biomarker Response To Joint Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of HA did not vary in marathoners, soccer players, and walkers [47,75]. Increased levels of COMP were reported in marathoners and walkers [52,[66][67][68]75], but remained unchanged in cyclists and volleyball players [53,54]. In soccer players [76,77], training induced fluctuations in the serum COMP levels during a competitive season.…”
Section: Other Proteinsmentioning
confidence: 87%
“…COMP consists of five identical glycoprotein subunits and is an extracellular cartilage matrix protein, interacting with collagen molecules to maintain the network ( Halász et al, 2007 ). Enhanced serum COMP levels have been reported in different joint diseases, like osteoarthritis ( Petersson et al, 1998 ; Clark et al, 1999 ), rheumatoid arthritis ( Lindqvist et al, 2005 ; Wisłowska and Jabłońska, 2005 ), and knee injuries ( Dahlberg et al, 1994 ), but also in response to physical activity ( Pruksakorn et al, 2013 ; Cattano et al, 2017 ; Roberts et al, 2018 ). For example, serum COMP concentration rises due to cyclic exercise after 30 min of walking ( Mündermann et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%